(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
In recent years we have seen intensive debates over the changes in scholarly practice caused by increased accessibility of digital resources and tools. This has caused an evident and rapid trend towards the development of different information behaviours by scholars: what information resources they are using, how and when. Recent studies of scholarly information behaviour all show significant changes in the ways researchers communicate, publish their works, collaborate, look for information and use it. Studies describe previously unseen patterns of scholarly information behaviour (e.g. skimming, navigating, power browsing, squirrelling, cross-checking). This, in turn, can (or should) have significant impact on the development of the information tools and information services for scholars. The paper first addresses key information concepts in scholarly context (e.g. information, information need, relevance, pertinence, salience, information overload, avoiding information), presents some general characteristics of scholarly information behaviour (e.g. difference between scholars and other users of information, differences between disciplines, individuals, etc.) and some typical examples of information behaviour (e.g. browsing, berrypicking, powerbrowsing, chaining, skimming, squirreling), as well as discusses some implications for information tools and services. In the end some attention is dedicated to issues of digital scholarship.